Program Parenting dalam Pendidikan Inklusi Anak TK Al Fawwaz Kids School di Kabupaten Tebo Provinsi Jambi - Trisni Herayati; Hera Gustina; Konny F Daisiu; Masita Nunlehu; Septi Endang Yunitasari (Student Journal of Early Childhood Education, 2023)
This study aims to describe and examine more deeply the services of parenting programs in inclusion education at Al Fawwaz Kids School Kindergarten in Tebo Regency, Jambi Province. This research is a descriptive research with a qualitative approach. The subjects of the study were principals and educators as organizers, parents and children with special needs. Data collection techniques with participant observation, interviews and documentation. The results of the study illustrate that the implementation is related to the planning, implementation and evaluation of parenting programs in Fawwaz Kids School Kindergarten. The implementation of parenting programs implemented in Fawwaz Kids School Kindergarten is often carried out using the method of lectures or discussions and holding private consultation sessions between special accompanying teachers and parents who have children with special needs. Evaluation of the parenting program is carried out periodically, namely weekly and incidental, namely every time you finish implementing the parenting program.